A method for testing dielectric properties of a material based on an electromagnetic bandgap structure resonant cavity

CN115616045BActive Publication Date: 2026-10-09XI AN JIAOTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211330295.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-27
Publication Date
2026-10-09
Estimated Expiration
2042-10-27

AI Technical Summary

Technical Problem

该方法测试时,由于需要两个完全一致的样品,制备起来较为困难,并且测试时需要用金属圆盘将样品夹紧以保证没有空气隙影响,因此不适用于易碎材料和保留铜电极的覆铜板测试

Benefits of technology

[0029] This invention provides a method for testing the dielectric properties of an electromagnetic bandgap resonant cavity. A rectangular resonant cavity is formed by enveloping periodically arranged metal pins, which overcomes the disadvantage that traditional rectangular resonant cavities cannot be tested in open cavity. Furthermore, the designed resonant cavity has a high quality factor and can achieve high-precision testing of the dielectric properties of materials in the z-axis direction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115616045B_ABST
    Figure CN115616045B_ABST
Patent Text Reader

Abstract

The application discloses a material microwave dielectric performance test method based on an electromagnetic band gap structure resonant cavity, and belongs to the field of material dielectric performance tests. 101 The resonant cavity is based on a traditional rectangular resonant cavity, the test sample is a sheet sample, the electromagnetic field mode in the cavity is TE 0000001 , the electric field direction is parallel to the thickness direction of the sample, and the dielectric performance in the thickness direction can be tested. A series of periodically arranged metal pins are arranged around each half cavity, according to the theory of gap waveguides and electromagnetic band gap structures, the surrounding metal pins form an electromagnetic band gap structure, when the thickness of the gap is less than one fourth of the working wavelength, by setting the size, height and spacing of the metal pins, the electromagnetic wave can be effectively suppressed from radiating outward from the gap, thereby meeting the requirements of the resonant method test. The application has the advantages of simple structure, convenient test, high cavity quality factor and more accurate test precision; and the separated design makes it more convenient to take and place materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of material dielectric property testing technology, and particularly relates to a precise testing method and research on the dielectric properties of materials. Background Technology

[0002] Dielectric materials have wide applications in daily life and production. With the rapid development of the communications field in recent years, the frequency range of their applications has gradually expanded from centimeter waves to millimeter waves. As the application frequency increases, the dielectric properties of materials have a greater impact on device performance. Furthermore, some materials exhibit anisotropy. Therefore, accurately testing the dielectric properties of materials in a specific direction is a crucial step in the initial circuit design process.

[0003] Traditional rectangular resonant cavities consist of metal walls, forming a sealed enclosure where electromagnetic waves resonate. Rectangular resonant cavities are simple in structure and their design technology is mature. However, because they are four-sided enclosed metal structures, testing requires placing appropriately sized samples of the material under test inside the cavity for sealed testing. Furthermore, the contact condition of the metal walls significantly impacts the performance of the rectangular resonant cavity; excessively large gaps between the metal walls can prevent the cavity from generating normal resonant modes.

[0004] Existing z-axis testing methods mainly include balanced disk resonator (BCDR) and microstrip circuit resonator.

[0005] The balanced disk resonator requires two identical circular sheet samples of the material under test before testing. During testing, a circular copper electrode is placed between the two samples, and then the three electrodes are placed in the center of the disk resonator and clamped together with a disk. This method is difficult to prepare because it requires two perfectly identical samples, and the metal disk is needed to clamp the samples to ensure no air gaps affect the test. Therefore, it is not suitable for testing fragile materials or copper-clad laminates with retained copper electrodes.

[0006] Microstrip resonators require fabrication of the material under test into a microstrip circuit during testing, thus limiting testing to easily processed materials. Furthermore, they have limitations in terms of applicable frequency and testing accuracy, making it impossible to test high frequencies and resulting in low testing precision.

[0007] Based on this, and to address the shortcomings of existing z-axis dielectric property testing techniques, this invention provides an electromagnetic bandgap resonant cavity. Summary of the Invention

[0008] The purpose of this invention is to realize a resonant cavity with an electric field direction that meets the requirements of z-axis testing, a high quality factor, and the ability to perform rapid testing.

[0009] To achieve the above objectives, the present invention employs a rectangular resonant cavity based on an electromagnetic bandgap structure. Therefore, based on the theory of gap waveguides, the present invention designs a rectangular resonant cavity using an electromagnetic bandgap structure. The gap waveguide consists of upper and lower metal plates and an electromagnetic bandgap structure between the metal plates. When the distance between the electromagnetic bandgap structures between the upper and lower metal layers is less than one-quarter of the operating wavelength, the electromagnetic bandgap structure can effectively prevent electromagnetic waves from propagating in the air gap between the electromagnetic bandgap structure and the upper layer; electromagnetic waves can only propagate between the electromagnetic bandgap structures. The electromagnetic bandgap structure can be formed in various ways; the present invention uses the method of machining metal pins on the metal plates to construct the electromagnetic bandgap structure.

[0010] A method for testing the dielectric properties of materials based on an electromagnetic bandgap resonant cavity, the specific steps of which are as follows:

[0011] Step 1: Establish the relationship between the resonant characteristics of the resonant cavity and the dielectric constant and dielectric loss of the sample;

[0012] The resonant frequency of the resonant cavity is related to the dielectric constant of the inserted sample, and the quality factor of the resonant cavity is related to the dielectric loss of the inserted sample. Therefore, the variation of resonant parameters when samples of different thicknesses and dielectric constants are inserted into the resonant cavity can be obtained beforehand through electromagnetic simulation software. By interpolating discrete data points, a three-dimensional surface showing the variation of the resonant cavity parameters with the sample's dielectric constant and thickness can be obtained. During actual testing, the measured data is substituted into the surface calculation to obtain the dielectric constant and dielectric loss of the sample under test. The relationship between the sample's dielectric constant and dielectric loss and the resonant characteristics is as follows:

[0013]

[0014]

[0015] Where, ε′ r ρ is the dielectric constant, tanδ is the loss tangent; f is the resonant frequency, Q is the quality factor, subscript 0 indicates the parameters in the cavity state, subscript s indicates the resonant parameters of the resonant cavity after the sample is loaded, h is the thickness of the sample to be tested, and K is the dielectric constant. ε and p es It's about ε′ r Functions of h.

[0016] For a specific resonant cavity, K s and p es It can be achieved through part of ε′ r The value is obtained by interpolation with the corresponding value of h.

[0017] Step 2: Set up the microwave testing system;

[0018] The testing system includes a network analyzer, a coaxial cable, and an electromagnetic bandgap resonant cavity; the electromagnetic bandgap resonant cavity is connected to the network analyzer via the coaxial cable.

[0019] Step 3: Test the cavity resonance characteristics;

[0020] Set the center of the network analyzer's scanning frequency to the design frequency of the resonant cavity, select an appropriate scanning bandwidth, and find the resonant peak of the resonant cavity, i.e., TE. 101 The resonant frequency and quality factor of the cavity are obtained.

[0021] Step 3: Test the resonance characteristics of the resonant cavity after adding the sample;

[0022] The sheet-like sample to be tested is placed horizontally in the gap in the middle of the resonant cavity. A new resonance peak is found using a network analyzer, and the resonant frequency and quality factor after the sample is loaded are obtained.

[0023] Step 4: Calculate the dielectric properties of the material based on the resonance characteristics of the resonant cavity before and after loading the sample;

[0024] Given the thickness h of the sample and the quality factor and resonant frequency of the resonant cavity before and after loading the sample, substitute each value into the formula in step 1 to calculate the dielectric constant and loss tangent of the material.

[0025] In step 3, the material to be tested must have a flat surface, uniform thickness, and a thickness not exceeding one-quarter of the wavelength corresponding to the test frequency.

[0026] In step 3, the transverse dimension of the material to be tested must be greater than 1.5 times the length a of the cuboid, and the longitudinal dimension must be greater than 1.5 times the width b of the cuboid.

[0027] In step 3, the relative permittivity of the material under test is selected in the range of 1 to 10, and the loss tangent is selected in the range of 0.0001 to 0.01.

[0028] The beneficial effects of this invention are as follows:

[0029] This invention provides a method for testing the dielectric properties of an electromagnetic bandgap resonant cavity. A rectangular resonant cavity is formed by enveloping periodically arranged metal pins, which overcomes the disadvantage that traditional rectangular resonant cavities cannot be tested in open cavity. Furthermore, the designed resonant cavity has a high quality factor and can achieve high-precision testing of the dielectric properties of materials in the z-axis direction. Attached Figure Description

[0030] Figure 1 This is a top view of an electromagnetic bandgap resonant cavity.

[0031] Figure 2 This is a cross-sectional view of an electromagnetic bandgap resonant cavity.

[0032] Figure 3 This is a schematic diagram of the test system;

[0033] Figure 4 Schematic diagram of a 28G electromagnetic bandgap resonant cavity;

[0034] Figure 5 Schematic diagram of a 10G electromagnetic bandgap resonant cavity;

[0035] Among them, 1 is a network analyzer, 2 is a coaxial cable, 3 is an electromagnetic bandgap resonant cavity, 4 is a metal pin in the resonant cavity, and 5 is the material under test. Detailed Implementation

[0036] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments.

[0037] This invention discloses a split rectangular resonant cavity based on an electromagnetic bandgap structure. A series of periodically arranged metal pins are placed on a metal plate, with rectangular regions in the center of each pin forming the rectangular resonant cavity. By changing the shape and size of the metal pins, the required bandgap of the resonant cavity can be altered. The performance of the electromagnetic bandgap structure can be obtained through simulation of corresponding one-dimensional and two-dimensional structures. In the specific design of the resonant cavity, increasing the pin size leads to a decrease in the stopband of the gap waveguide. Therefore, as the resonant frequency of the cavity increases, the size of the metal pins, including their side length and height, needs to be reduced.

[0038] The specific design structure of the electromagnetic bandgap resonant cavity is as follows: Figure 1 As shown, a rectangular region with length a and width b is on a metal plate. The ratio of a to b ranges from (1:1) to (3:1). The specific values ​​of a and b are determined by the design frequency of the resonant cavity. Generally, in the frequency range of the resonant cavity from 1G to 39G, the value of a ranges from 5mm to 40mm, and the value of b ranges from 2mm to 20mm. The region is surrounded by periodically arranged metal pins. Specifically, in the direction of length a, the number of periods m of the metal pins is not less than 6 and not more than 30, and in the direction of length b, the number of periods n of the metal pins is not less than 4 and not more than 20. The metal pins are of uniform size, and the height of each metal pin is h, with the value of h ranging from 4mm to 20mm. The cross-sectional shape of the metal pins includes, but is not limited to, square, rectangle, and circle. They are arranged periodically at equal intervals in a two-dimensional direction. The center distance between two adjacent pins in the front, back, left, and right directions is p, with the value of p ranging from 1mm to 20mm.

[0039] The above structure is a semi-cavity construction, with two semi-cavities placed facing each other, such as... Figure 2As shown, a fixed gap of thickness D is reserved in the middle through a mechanical structure. The value of D depends on the operating frequency of the resonant cavity. Generally, the size of D is one-quarter of the operating wavelength. In the center of the device, a cuboid is generated by the envelopment of metal pins, which is the rectangular resonant cavity. This is the part of the resonant cavity that generates resonance. During testing, the size of the material to be tested needs to be able to cover this part of the area. The above is the basic structure of the electromagnetic bandgap resonant cavity.

[0040] The resonant cavity designed using this method follows the resonance law of a rectangular resonant cavity, and the test mode uses the dominant mode TE of the rectangular resonant cavity. 10n In this mode, the electric field is concentrated in the central region of the resonant cavity, perpendicular to the z-axis. The quality factor of the cavity is almost identical to that of a traditional rectangular resonant cavity. Taking a 10G cavity as an example, the quality factor of a traditional rectangular resonant cavity is around 8000, while the quality factor of the electromagnetic bandgap resonant cavity designed using this method is around 6700. This method overcomes the limitation of traditional rectangular resonant cavities not being able to be tested with open cavities. Compared to other methods for testing dielectric properties along the z-axis, this method has a simpler testing process and higher testing accuracy.

[0041] Example 1

[0042] A series of periodically arranged metal pins are placed on a metal plate. The rectangular region in the middle of the metal pins forms a rectangular resonant cavity. By changing the shape and size of the metal pins, the bandgap required by the resonant cavity can be changed. The performance of the electromagnetic bandgap structure is obtained by simulating the corresponding one-dimensional and two-dimensional structures. In the specific design of the resonant cavity, the stopband of the gap waveguide will decrease as the size of the pins increases. Therefore, as the resonant frequency of the resonant cavity increases, the size of the metal pins, including their side length and height, needs to be reduced.

[0043] The electromagnetic bandgap resonant cavity consists of two half-cavities, each made of a metal with high conductivity. At the center of the metal plate is a rectangular region with length *a* and width *b*, where the ratio of *a* to *b* ranges from (1:1) to (3:1). The specific values ​​of *a* and *b* are determined by the design frequency of the resonant cavity. Generally, within the frequency range of 1 GHz to 39 GHz, the value of *a* ranges from 5 mm to 40 mm, and the value of *b* ranges from 2 mm to 20 mm. The rectangle is surrounded by periodically arranged metal pins. In the direction of length a, the number of cycles m of the metal pins is not less than 6 and not more than 30. In the direction of length b, the number of cycles n of the metal pins is not less than 4 and not more than 20. The metal pins are of the same size, and the height of each metal pin is h, with the value of h ranging from 4mm to 20mm. The cross-sectional shape of the metal pins includes, but is not limited to, square, rectangle, and circle. They are arranged periodically at equal intervals in the two-dimensional direction. The center distance between two adjacent pins in front, behind, left, and right is p, with the value of p ranging from 1mm to 20mm.

[0044] The above structure is a half-cavity construction, with two half-cavities placed facing each other, and a fixed gap of thickness D reserved in the middle by a mechanical structure. The value of D depends on the operating frequency of the resonant cavity. Generally, the size of D is one-quarter of the operating wavelength. In the center of the device, a cuboid is generated by the envelopment of a metal pin, which is the rectangular resonant cavity. This is the part of the resonant cavity that generates resonance. During testing, the size of the material to be tested needs to be greater than 3 / 2 of the area of ​​this part. The above is the design model of the electromagnetic bandgap structure resonant cavity.

[0045] The resonant cavity designed using this method follows the resonance law of a rectangular resonant cavity, and the test mode uses the dominant mode TE of the rectangular resonant cavity. 101 The electric field in this mode is concentrated in the central region of the resonant cavity, perpendicular to the z-axis. The quality factor of the cavity is close to that of a traditional rectangular resonant cavity. Taking a 10G cavity as an example, the quality factor of a traditional rectangular resonant cavity is around 8000, while the quality factor of the electromagnetic bandgap resonant cavity designed using this method is around 6700, far exceeding that of the traditional z-axis testing method, the microstrip line method. This method overcomes the limitation of traditional rectangular resonant cavities not being able to be tested with open cavities. Compared to other z-axis dielectric property testing methods, this method has a simpler testing process and higher testing accuracy.

[0046] This embodiment provides a method for testing the dielectric properties of materials in a 28G electromagnetic bandgap resonant cavity, such as... Figure 4 The diagram shows the main testing instruments, which are a 28G electromagnetic bandgap resonant cavity and a network analyzer. The material being tested is 0.3mm fused silica glass. (Relative permittivity ε′) r =3.8, loss tangent tanδ=0.0002),

[0047] The design parameters for the 28G electromagnetic bandgap resonator are as follows: the size of the central region a is 18mm, the size of b is 8mm, the metal pins used have a cross-sectional side length w of 1.5mm, a spacing p of 4mm, a period number m in the length a direction of 9, a period number in the length b direction of 5, and a gap thickness of 0.4mm. The testing steps for this frequency resonator are as follows:

[0048] Step 1: Establish the relationship between the resonant characteristics of the resonant cavity and the dielectric constant and dielectric loss of the sample;

[0049] The resonance characteristics of the simulated cavity and the loaded sample are analyzed, and K is expressed by the following formula. ε and p es Perform interpolation calculations to obtain K. ε and p es Corresponding to a three-dimensional curved surface.

[0050]

[0051]

[0052] Step 2: Set up the microwave testing system;

[0053] The testing system includes a network analyzer, a coaxial cable, and an electromagnetic bandgap resonant cavity; the electromagnetic bandgap resonant cavity is connected to the network analyzer via the coaxial cable.

[0054] Step 3: Test the cavity resonance characteristics;

[0055] The network analyzer's scanning frequency center was set to 28 GHz, and the scanning bandwidth was selected as 1 GHz. The resonant peak of the resonant cavity was found, and the cavity's resonant frequency of 28.432 GHz and quality factor of 3912 were obtained.

[0056] Step 4: Test the resonance characteristics of the resonant cavity after adding the sample;

[0057] A 0.3 mm fused silica glass was placed horizontally in the gap in the middle of the resonant cavity. The resonant peak was found using a network analyzer, and the resonant frequency after loading the sample was obtained as 27.041 GHz and the quality factor as 3682.

[0058] Step 5: Calculate the dielectric properties of the material based on the resonance characteristics of the resonant cavity before and after loading the sample;

[0059] Given the sample thickness h = 0.3 mm and the quality factor and resonant frequency of the resonant cavity before and after sample loading, the values ​​were input into the calculation software. The calculated dielectric constant and loss tangent of the material were 3.78 and 1.8 × 10⁻⁶, respectively. -4 Compared with the standard value, the test results of this system for quartz glass are within the standard range, and the test results are reliable.

[0060] Example 2

[0061] This embodiment provides a method for testing the dielectric properties of materials in a 10G electromagnetic bandgap resonant cavity, such as... Figure 5 The diagram shows the main testing instruments: a 10G electromagnetic bandgap resonant cavity and a network analyzer. The material being tested is 1mm fused silica glass. (Relative permittivity ε′) r =3.8, loss tangent tanδ=0.0002),

[0062] The design parameters for the 10G electromagnetic bandgap resonator are as follows: the size of the central region a is 20mm, the size of b is 20mm, the metal pins used have a cross-sectional side length w of 4mm, a spacing p of 8mm, a period number m in the length a direction of 9, a period number b in the length b direction of 9, and a gap thickness of 1.5mm. The testing procedure for the resonator at this frequency is similar to that in Example 1.

[0063] The test results showed that the resonant frequency of the cavity was 10.454 GHz and the quality factor was 6248. After loading the sample, the resonant frequency was 10.008 GHz and the quality factor was 5920. Given a sample thickness of h = 1 mm, the values ​​were input into calculation software, and the calculated dielectric constant and loss tangent of the material were 3.77 and 1.8 × 10⁻⁶, respectively. -4 Compared with the standard value, the test results of this system for quartz glass are within the standard range, and the test results are reliable.

[0064] The above description is merely a specific embodiment of the present invention. Any feature disclosed in this specification may be replaced by other equivalent or similar features unless otherwise specified. All features or steps in the disclosed methods or processes may be combined in any way, except for mutually exclusive features and / or steps.

Claims

1. A method for testing the dielectric properties of materials based on an electromagnetic bandgap resonant cavity, characterized in that: The steps are as follows: Step 1: Establish the relationship between the resonant characteristics of the resonant cavity and the dielectric constant and dielectric loss of the sample; The resonant frequency of the resonant cavity is related to the dielectric constant of the inserted sample, and the quality factor of the resonant cavity is related to the dielectric loss of the inserted sample. Through electromagnetic software simulation, the variation of resonant parameters when samples of different thicknesses and dielectric constants are inserted into the resonant cavity is obtained. Based on discrete data point interpolation, a three-dimensional surface is obtained showing the variation of the resonant cavity parameters with the sample's dielectric constant and thickness. During actual testing, the measured data is substituted into the surface for calculation to obtain the dielectric constant and dielectric loss of the sample under test. The relationship between the sample's dielectric constant and dielectric loss and the resonant characteristics is as follows: in, Where is the dielectric constant. The value is the loss tangent; f is the resonant frequency; Q is the quality factor; the subscript 0 indicates the parameters in the cavity state; the subscript s indicates the resonant parameters of the cavity after the sample is loaded; and h is the thickness of the sample to be tested. and It is about Functions of h; For a specific resonant cavity and Through part The value is obtained by interpolation with the corresponding value of h; Step 2: Set up the microwave testing system; The test system includes a network analyzer, a coaxial cable, and an electromagnetic bandgap resonant cavity; the electromagnetic bandgap resonant cavity is connected to the network analyzer via the coaxial cable. Step 3: Test the cavity resonance characteristics; Set the center of the network analyzer's scanning frequency to the design frequency of the resonant cavity, select a scanning bandwidth of 1 GHz, and find TE. 101 After the resonance peak, the scanning bandwidth is reduced with the resonance peak frequency as the center, so that the 3dB bandwidth range of the resonant cavity occupies 2 / 3 of the entire scanning bandwidth, and the accurate cavity resonant frequency and quality factor are read from the network analyzer. Step 4: Test the resonance characteristics of the resonant cavity after adding the sample; The sheet-like sample to be tested is placed horizontally in the gap in the middle of the resonant cavity. A new resonance peak is found using a network analyzer, and the resonant frequency and quality factor of the resonant cavity are read after the sample is loaded. The material to be tested must have a flat surface, uniform thickness, and a thickness not exceeding one-quarter of the wavelength corresponding to the test frequency. The transverse dimension of the material to be tested must be greater than 1.5 times the length a of the cuboid, and the longitudinal dimension must be greater than 1.5 times the width b of the cuboid; Step 5: Based on the resonant frequency and quality factor of the resonant cavity before and after the sample loading obtained from the test, calculate the dielectric properties of the material by interpolation and table lookup. Given the thickness h of the sample and the quality factor and resonant frequency of the resonant cavity before and after loading the sample, substitute each value into the formula in step 1 to calculate the dielectric constant and loss tangent of the material. An electromagnetic bandgap resonant cavity is located on a metal plate in a rectangular region with length *a* and width *b*. The ratio of *a* to *b* ranges from (1:1) to (3:1). The specific values ​​of *a* and *b* are determined by the design frequency of the resonant cavity. Within the frequency range of the resonant cavity from 1 GHz to 39 GHz, the value of *a* ranges from 5 mm to 40 mm, and the value of *b* ranges from 2 mm to 20 mm. The cavity is surrounded by periodically arranged metal pins. In the direction of length *a*, the number of periods *m* of the metal pins is not less than 6 and not more than 30. In the direction of length *b*, the number of periods *n* of the metal pins is not less than 4 and not more than 20. The metal pins are of uniform size, and the height of each metal pin is *h*, which ranges from 4 mm to 20 mm. The cross-sectional shape of the metal pins is square, rectangular, or circular. They are arranged periodically at equal intervals in a two-dimensional direction. The center distance between two adjacent pins is *p*, which ranges from 1 mm to 20 mm. The above structure is a half-cavity construction, with two half-cavities placed facing each other, and a fixed gap of thickness D reserved in the middle by a mechanical structure. The value of D depends on the operating frequency of the resonant cavity, and the size of D is one-quarter of the operating wavelength. In the center of the device, a cuboid is generated by the envelopment of metal pins to form a rectangular resonant cavity.

2. The method according to claim 1, characterized in that, In step 3, the relative permittivity of the material to be tested is selected in the range of 1 to 10.

3. The method according to claim 1, characterized in that, In step 3, the loss tangent of the material to be tested is selected within the range of 0.0001~0.01.

Citation Information

Patent Citations

  • Method for measuring microwave dielectric properties of high-loss material by adopting electric field symmetrical structure

    CN111157802A